2016
DOI: 10.3354/aei00191
|View full text |Cite
|
Sign up to set email alerts
|

Carbon, nitrogen and phosphorus budgets of silver carp Hypophthalmichthys molitrix with the co‑culture of grass carp Ctenopharyngodon idella

Abstract: Fish farming activities have resulted in increasing nutrient pollution and subsequent deterioration of water quality in aquatic environments worldwide. Silver carp Hypophthalm ichthys molitrix can efficiently remove excessive nutrient pollution by filtering the suspended particulate organic matter. To evaluate the feasibility and capacity of using silver carp as biofilters to remove the wastes released from the farming of grass carp Ctenopharyngodon idella, 3 mesocosms comprising grass carp and silver carp wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Ramos et al (2013) have investigated A. lacustris feeding on diet composed of insect fragments; they observed this very same pattern and vegetable fragments in natural environment. Astyanax lacustris is considered omnivorous (Pereira et al, 2016) and its high ration intake can indicate the likely ability to buffer the ration input into the environment as biofilter, as observed in other studies (Felsing et al, 2005;Ramos et al, 2008;Xia et al, 2016). However, it is worth emphasizing that this condition should not be used as isolated solution to control artificial feed import.…”
Section: Discussionmentioning
confidence: 79%
“…Ramos et al (2013) have investigated A. lacustris feeding on diet composed of insect fragments; they observed this very same pattern and vegetable fragments in natural environment. Astyanax lacustris is considered omnivorous (Pereira et al, 2016) and its high ration intake can indicate the likely ability to buffer the ration input into the environment as biofilter, as observed in other studies (Felsing et al, 2005;Ramos et al, 2008;Xia et al, 2016). However, it is worth emphasizing that this condition should not be used as isolated solution to control artificial feed import.…”
Section: Discussionmentioning
confidence: 79%
“…These results show that analysis of the N and P budget in an aquaculture system is an effective way to evaluate the importance of nutrient sources, material conversion efficiency and pollution level in the system (Honda & Kikuchi, ). In a pond culture system, organisms usually have low N and P utilization rates (generally 20%–47% and 8%–24% respectively) (Guo, Zhao, Wang & Dong, ; Xia, Sun, Gao, Dong & Wang, ; Zhang et al., ). In the recirculating aquaculture systems in this study, N and P utilization rates by abalones were 35.06%–54.18% and 9.33%–20.35% respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The biodeposition of particulate P in water caused by the grazing of silver carp and bivalves may be a reason why the content of water P did not increase. Previous studies have shown that silver carp and bivalves could promote the removal of water nutrients by grazing on suspended particles or algae and then excreting food residue or feces at the sediment surfaces [29][30]. When this transfer rate is greater than the release rate of nutrients from sediments to water, the water nutrient load will decrease and the eutrophication process will be slowed down.…”
Section: Mechanisms Of Combined Biological Restorationmentioning
confidence: 99%
“…However, the monitoring results of water quality and sediment TN content showed that the TN contents increased in the sediments while decreasing in the water. One possible reason is that the biodeposition of silver carp and bivalves accelerated the transformation of particulate N from water into the sediments [29][30]. The silver carp and bivalves could filter suspended particles and algae from water, and then excrete the feces or pseudofeces into the water or the sediment surface.…”
Section: Mechanisms Of Combined Biological Restorationmentioning
confidence: 99%